Mediterranean diet and prime diet quality score are associated with reduced risk of premature coronary artery disease in Iran: a multi-centric case-control study - Noushin Mohammadifard; Mehran Rahimlou; Reza Amani-Beni; Bahar Darouei; Ehsan Zarepur; Fahimeh Haghighatdoost; Sharareh Nazemzadeh-Harandi; Nahid Azdaki; Nahid Salehi; Masoud Lotfizadeh; Samad Ghaffari; Arsalan Salari; et al. (Scientific Reports)
Abstract The Mediterranean diet (Med-Diet) is widely recognized for its protective effect in cardiovascular diseases (CVDs), less is known about the associations between health and adherence to the Prime Diet Quality Score (PDQS). This study investigates the relationship between adherence to the Med-Diet and PDQS with the risk of premature coronary artery disease (PCAD) in an Iranian population. A total of 3287 participants were included in this multicenter case-control study across various ethnic groups in Iran, categorized into PCAD cases (n = 2106) and controls (n = 1181). PCAD cases were defined as individuals with at least one coronary artery exhibiting ≥ 75% stenosis or a left main coronary artery with ≥ 50% stenosis, while controls had normal coronary arteries. Dietary intake was assessed using a semi-quantitative food frequency questionnaire (FFQ), previously validated for accuracy in the Iranian population Adherence to the Med-Diet was assessed using a standardized scoring system, awarding one point for higher consumption of beneficial food groups (such as vegetables, whole grains, legumes, fish, nuts, and a high monounsaturated-to-saturated fat ratio) and one point for lower consumption of less favorable foods (such as red and processed meats). The total score ranged from 0 to 9, with higher scores indicating greater adherence to the Med-Diet. The PDQS, a dietary quality index, evaluated adherence across 14 healthy and 7 unhealthy food groups, with higher scores reflecting better diet quality. Logistic regression models were employed to examine the association between dietary scores and PCAD risk. Participants with higher adherence to both the Med-Diet and PDQS had significantly lower odds of PCAD (OR = 0.30, 95% CI: 0.22, 0.40; P for trend < 0.001 for PDQS), with a stronger association observed for the Med-Diet (OR = 0.08, 95% CI: 0.06, 0.10; P for trend < 0.001). Additionally, higher adherence to the Med-Diet (OR = 0.04, 95% CI 0.03, 0.05) and PDQS (OR = 0.21, 95% CI: 0.17, 0.26) was inversely associated with PCAD severity in the fully adjusted model. This study showed a protective association of the Med-Diet and PDQS with reduced risk of PCAD in the Iranian population.